LEGAL FEELING AS A COMPONENT OF A LAW ENFORCEMENT ACTIVITY OF PUBLIC AUTHORITIES - Kаliuzhnyj Rostyslav; Shapenko, Liudmyla (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: of the article is an investigation of the essence of such notion as «legal feeling» as an essential element during law enforcement realization by public authorities and also the characteristic of its role and value for providing the legal regulation mechanism in general. Methods of research: methodology base of research includes hard science and specially legal methods of recognizion, the using of such methods allowed to analyze different conceptual approaches to the creating ideas as for correlation of intelligence and insight, legal feeling impact, legal emotions and thinking on the process of recognizion and using law. Results: the result of such scientific work became the development of theoretical provisions, due to which the definition of legal feeling was formed as a socio psychological (emotional) human attitude to the law, legal validity, legal attribution and adjustments, based on universally recognized ideal of goodness and justice.It was also proved by authors the meaning of legal feeling for construction and functioning of integrated, effective and inclusive system of public authorities, in particular due to its ability to implement the law into more powerfull instrument, which is capable for providing social justice and keeping rule of law. Discussion: legal feeling is a compound socio psychological phenomenon which exist in every individual, society in general throught the history of its development. Its role in modern conditions may and must be strenghened in all areas, as it is one of the important prerequsites for creation of legal state and democratic society. Researched scientific ideas have an important meaning for implementation of public authority work. Its implementation in the process of accepting legal decisions causes the development of emotional intelligence and motivate employees of public authorities pay attention to their professional etiquette, it contributes a sign of respect toward people, spreading a social access to justice, their opportunity to take part in public rights management.